Peran Komunikasi Orang Tua dalam Mengawasi Penggunaan Media Sosial oleh Anak di Desa Pondok Beringin - Nuzuli, Ahmad Khairul; Rimin, Rimin; Aldian, Sandri; Mariana, Suci; Aulia, Tesa (BINA' AL-UMMAH, 2024)
This study aims to examine the role of parental communication in supervising and guiding children's use of social media in Pondok Beringin Village, Kerinci Regency. The research focuses on understanding the challenges, strategies, and influence of parental communication on children's digital literacy. The study employs a qualitative method with a descriptive approach. Data were collected through interviews and observations, involving five informants selected using purposive sampling based on the relevance of their information. The findings reveal several key challenges faced by parents, including a lack of technological understanding, limited time for supervision, social environmental influences, and children's difficult behavior. To address these challenges, proposed strategies include open communication, active supervision, clear rule implementation, education on digital ethics, and the use of monitoring applications. Social factors, such as community norms and peer influence, also affect parental communication patterns in supervision. The study concludes that effective communication between parents and children can minimize the negative impacts of social media and enhance children's digital literacy. Moreover, collective education within local communities is highlighted as a crucial strategy to create a safe and healthy digital environment for children